Feelings and emotions: the Loyola Symposium - Arnold, Magda B. (Personality and psychopathology, 1970)
Feelings and Emotions: The Loyola Symposium covers knowledge in the field of emotion. The book discusses the theories of emotions based on biological considerations; the neural and physiological correlates of feeling and emotion; and cognitive theories of feeling and emotion. The text also describes the psychological approaches to the study of emotion; the mood theory and measurement; as well as the developments related to the search for significant relations between private events and both behavioral and physiological events. The role of feelings and emotions in personality is also encompass.